EFFICACY OF FUNGICIDES AND BIO-CONTROL AGENTS AGAINST SCLEROTIUM ROLFSII CAUSING STEM ROT OF SOYBEAN UNDER NEH REGION OF INDIA (Journal of Plant Disease Sciences, 2017)
Soybean [ (L.) Merrill], Glycine max 'Queen of Pulses,' a native of Eastern Asia belongs to the family Leguminosae, sub family Papilionoideae and tribe Phaseolae is a worldwide economic crop and the most important cultivated legume with hundreds of food, feed and industrial uses. Sclerotium rolfsii is an omnivorous soil-borne fungal pathogen and causes disease in a wide range of agricultural and horticultural crops. It has at least 500 species hosts in 100 families (Ferreira and Boley, 1992). The most common hosts are legumes, cruciferous and cucurbits. The diseases caused by the fungus are more serious in tropical and sub-tropical regions.
Keywords: Soybean, fungicides, bio-control agents and stem rot. Sclerotium rolfsii